Development and testing of a new type of "barefoot running shoe": The freeheel runningpad - Daumer, M. (International Calgary Running Symposium, August 14-17, 2014, 2014)
Background: Common barefoot running shoes or minimal footwear have one or several of the following properties/deficiencies, depending on the type and brand and personal taste: - Coverage of a considerable fraction of the foot.s surface with textile/plastic leading to sub-optimal foot climate (overheating, sweating, odor) - Considerable weight for a true barefoot shoe - Toe pockets that do not fit with non-standard feet - Considerable size and thickness, in particular in the heel section of the protective sole for a true barefoot shoe - Positive drop and therefore a change in the biomechanics compared to barefoot running We wanted to design a new type of shoe that would be as close as possible to real barefoot running and thereby overcome one or several of these perceived deficiencies. Whether this would lead to a reduction or increase in running related injuries and how to best train with the new shoes is not within the scope of this article.